Undeclared exposure to St. John's Wort in hospitalized patients - Martin-Facklam, Meret; Rieger, Karin; Riedel, Klaus-Dieter; Burhenne, Jürgen; Walter-Sack, Ingeborg; Haefeli, Walter E. (British journal of clinical pharmacology, 2004)
Aim The herbal medicine St. John's Wort (SJW) causes substantial decreases in the plasma concentrations of a range of co-administered drugs. Therefore, we evaluated the extent of systemic exposure to hyperforin and hypericin, two of the main constituents of SJW, in patients on admission and during hospital stay, and compared the results with known use of SJW as documented in the drug chart and detected in additional interviews. Methods One hundred and fifty patients aged ≥ 18 years and admitted, between August 2000 and February 2002, to an internal medicine ward of a large German university hospital were included. Hyperforin and hypericin was determined in plasma by a sensitive liquid chromotography/mass spectometry (LC/MS/MS) method. To assess undeclared use of SJW the data were compared to information obtained from drug charts and from up to three interviews that had a particular focus on intake of herbal medicines and self-medication during hospitalization. Results Hyperforin was detected in 12 patients (plasma concentration on the first day of hospitalization = 12-100 ng ml−1 in five patients and <3 ng ml−1 in seven), and hypericin in five patients (0.5-4.3 ng ml−1). Nine patients (6%) were taking/had taken SJW without the knowledge of the medical team and the pharmacist, who conducted the additional interviews, and 11 (7.3%) were taking/had taken SJW without the knowledge of the medical team alone. Seven of these patients were treated concurrently with drugs that can interact with SJW. Conclusions Unrecognized use of SJW is frequent and may have an important influence on the effectiveness and safety of drug therapy during hospital stay.
Gesehen am 19.05.2021